PENGEMBANGAN E-BOOK TATA RIAS PENGANTIN TORAJA MENINGKATKAN KETERAMPILAN DAN HASIL BELAJAR MAHASISWA PADA JURUSAN PENDIDIKAN KESEJAHTERAAN KELUARGA KONSENTRASI TATA RIAS FAKULTAS TEKNIK UNM - Burhanuddin, Izmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of the Toraja bridal makeup e-book aims to improve the skills and learning outcomes of students in the Family Welfare Education Department, with a concentration in Makeup, at the Faculty of Engineering, Universitas Negeri Makassar. This e-book has been designed as an interactive and accessible learning medium, providing comprehensive material on Toraja bridal makeup, from the theoretical aspects of Toraja wedding traditions to the practical application steps. The use of this e-book in bridal makeup learning is expected to facilitate students in understanding and mastering the complex makeup techniques while enriching their knowledge of local culture. The Toraja Bridal Makeup E-Book serves as a learning guide, addressing the lack of such resources in the teaching process. The research method and design follow the ADDIE model, developed by Dick and Carey. The results indicate that using this e-book significantly improves students' practical skills in Toraja bridal makeup and enhances their overall learning outcomes. This e-book is anticipated to become an effective and relevant learning innovation in line with technological advancements and the demands of the beauty industry.